Palm-oil thorn induced granulomatous lesion with aseptic arhthritis - Che Ahmad, Aminudin; Zulkifly, Ahmad Hafiz; Sa'at@Yusof, Azlin (Faculty of Medicine, International Islamic University Malaysia, 2003)
Palm-oil thorn granulomatous lesion is an overlooked cause of joint arthritis. The natural history is unique but most of the investigations are inconclusive. We presented a case of aseptic arthritis developed in the elbow following injury by palm-oil thorn.